Heterogeneity in the relationship between the built environment and driving: Focus on neighborhood type and travel purpose. (October 2015) - Salon, Deborah
Abstract: Global concern about fossil fuel use and associated environmental externalities has led many governments to consider actions that encourage their residents to drive less. This research uses empirical analysis of travel survey data to estimate the relationship between built environment characteristics and vehicle miles traveled (VMT) in California. The work improves upon past research in two key ways. First, it employs a novel approach to control for residential self-selection, categorizing neighborhoods into types and using these as the alternatives in a predictive model of neighborhood type choice. Second, it focuses on exploring and understanding heterogeneity in the relationship between the built environment and VMT across two dimensions – neighborhood type and travel purpose. The results show that VMT sensitivity to built environment characteristics does depend on both neighborhood type and the purpose of travel, in ways that are intuitive but had not previously been estimated. This calls into question the usefulness of prior research that provides only single point estimates of the relationships between travel choices and the built environment. Though these relationships may be small on average, this work shows that for certain trip types and in certain neighborhood types, the built environment is strongly related to travel choices.